A Theology of Reconciliation - Mattam, Joseph (Asian Horizons, 2024)
Reconciliation is an important dimension of our mission which is to build communities of love and unity. If we look at Mission as the proper loving human relationship that enriches and empowers everyone, then reconciliation is an essential component of this process. For we live in a divided world, causing and suffering from various forms of divisions. In this paper I shall look first at the world of division, then see the attempts at reconciliation in various cultures and religions, and then look at the essentials of this process of reconciliation and the areas that need reconciliation.